2016
DOI: 10.1016/j.nbd.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cognitive discrimination and discoordination of coupled theta–gamma oscillations in Fmr1 knockout mice

Abstract: Fragile X syndrome (FXS) patients do not make the fragile X mental retardation protein (FMRP). Absence of FMRP causes dysregulated translation, abnormal synaptic plasticity and the most common form of inherited intellectual disability. But FMRP loss has minimal effects on memory itself, making it difficult to understand why absence of FMRP impairs memory discrimination and increases risk of autistic symptoms in patients, such as exaggerated responses to environmental changes. While Fmr1 knockout (KO) and wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 119 publications
(165 reference statements)
9
84
0
Order By: Relevance
“…Similar to findings in Fmr1 KO mouse cortex [34], we found a shift toward reduced influence of alpha frequency oscillations on gamma power and synchronization in FXS compared to controls. Cortical networks in healthy controls generally utilize alpha oscillations to control and inhibit local network excitation [45]; in FXS, these networks may rely more consistently on slower theta waves or even delta waves (see Additional file 1) to modulate gamma frequency, given the lack of deficit in theta-gamma coupling.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to findings in Fmr1 KO mouse cortex [34], we found a shift toward reduced influence of alpha frequency oscillations on gamma power and synchronization in FXS compared to controls. Cortical networks in healthy controls generally utilize alpha oscillations to control and inhibit local network excitation [45]; in FXS, these networks may rely more consistently on slower theta waves or even delta waves (see Additional file 1) to modulate gamma frequency, given the lack of deficit in theta-gamma coupling.…”
Section: Discussionsupporting
confidence: 89%
“…Theta and alpha band modulation of gamma activity were of particular interest, as previous studies have suggested theta and alpha abnormalities in FXS patients [32, 33] and KO rodent models [34]. Frequency bands of interest were chosen as follows based on standard low-frequency and gamma band cut-offs: theta, 4–7 Hz; alpha, 8–12 Hz; gamma, 30–80 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Place avoidance tasks are rapidly learned and sensitive to hippocampus dysfunction (Cimadevilla et al, 2000;Cimadevilla et al, 2001b). The experience of mild foot shock in a particular location induces place avoidance memories that require persistent hippocampal LTP and causes changes in hippocampal synaptic network function that persist for at least a month (Cimadevilla et al, 2001b;Pastalkova et al, 2006;Burghardt et al, 2012;Kheirbek et al, 2013;Park et al, 2015;Pavlowsky et al, 2016;Radwan et al, 2016). Because stress is known to modify synaptic plasticity and memory-related biochemical signaling (Korz and Frey, 2003;Ahmed et al, 2006), it is of substantial importance to determine to what extent place avoidance training is stressful.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for this could be that although the coordination of spikes between place cells are lowered in the knockout mice to a level that the phase-distance relationship is lost, there is still a significant enough level of theta modulation of the neurons that some structure in the distribution of phases remains. In any case, further work should address whether this phase code, relevant at behavioural timescales, is needed for long-term memory formation of independent representations of spatially informed tasks, since knock-out mice present deficiencies when required to perform discrimination tasks of past events with a spatial component, as opposed to performing as well as wild-type mice at learning and retaining unchanging spatial information (Radwan et al, 2016;Kooy et al, 1996;Krueger et al, 2011).…”
Section: Discussionmentioning
confidence: 99%